Humanismo como ética: um estudo sobre a alteridade em Emmanuel Lévinas - Agripino, Valdezia Izidorio (2014)
The present work is mainly aimed to present a study on the issue of otherness and the humanism in the work of Emmanuel Levinas. The guiding point of this research focuses on commitment to withdraw the philosopher's ontological ethics field and as a consequence to appoint a new sense of humanity. Levinas noted that his time stood before an ethics crisis devaluation of human life caused by solipsistic paradigms mainly on the political middle .Selfishness is appointed by him as the main cause of the ills of society in which each individual seeks his own benefits without thinking of the horrors that can cause other men. Levinas realizes that human relationships cannot be said through selfish and monologic discourses, in which the self is placed at the center of philosophical arguments. That is how humanism can stand on a significance that is revealed in the face of another man, not as total ethical phenomenon in a responsible face which enables the ethics to take the place of prima philosophia.Thus, new ethical perspective is showed, the one of responsibility for the needs of others. The man is the ultimate meaning of his writings, directed to a new way of conceiving ethics. The levinasian philosophy reaches the metaphysical or ethical field in the Face of the Other human being. Breaking with the order of the whole , i.c. , the ontology of war. Levinas shows new ways in which totalitarian philosophy in which himself proposes the other in an arbitrary shape, can be replaced by an ethical- philosophical discourse not described by the fundamentals of ontology. This proposal takes an argumentative way with the idea of the infinite Cartesian which enables a break with completeness. The philosophical proposal by Levinas seeks to build a knowledge that respects differences and welcome the otherness in which the Other remains as an another, as a foreigner, without reducing it to an object. The levinasian humanism is humanism of the other man.